NEONATAL OUTCOME IN PATIENTS WITH SEVERE PRE-ECLAMPSIA DURING 28-34 WEEKS OF GESTATION - Attiya Muzzammil; Mubashra Naz; Muzzammal Iftikhar; Umber Fatima; Humaira Zafar (Journal of University Medical & Dental College, 2019)
Pre-eclampsia is an unpredictable multi-organ syndrome that pregnant women develops. It is associated with signiﬁcant maternal and fetal morbidity and death worldwide. Treatment of this syndrome remains a diﬃcult task to even the most experienced obstetricians, mainly because the exact etiology is unknown.OBJECTIVE: To determine neonatal outcome in patients with severe preeclampsia between 28-34 weeks of gestation with conservative treatment.MATERIAL & METHODS: It was descriptive case study. Duration of study was 6 months from October 2010 to March 2011. The study was conducted in gynae unit D.H.Q Hospital Faisalabad. Total admitted 109 pregnant women with severe preeclampsia (P.E) were included in study after fulﬁlling inclusion criteria. Fetal & maternal surveillance was carried out as per set protocol. Steroids were given for fetal lung maturity. Uncontrolled hypertension despite of maximum doses of two antihypertensives, imminent eclampsia, placental abruption and fetal compromise were considered as indication of urgent delivery.RESULTS: According to this study, mean age of the patients was 23 years and mean gestational age was 32 weeks. Average birth weight was 1613 grams, APGAR score at 1 minute was 5.33 and neonatal mortality was 11.9%.CONCLUSION: The expectant management in women with severe pre-eclampsia between 28 and 34 weeks gestation is associated with better Neonatal out come.